2022
DOI: 10.3390/jcm11206109
|View full text |Cite
|
Sign up to set email alerts
|

Admission Predictors of Mortality in Hospitalized COVID-19 Patients—A Serbian Cohort Study

Abstract: Background: Early prediction of COVID-19 patients’ mortality risk may be beneficial in adequate triage and risk assessment. Therefore, we aimed to single out the independent morality predictors of hospitalized COVID-19 patients among parameters available on hospital admission. Methods: An observational, retrospective–prospective cohort study was conducted on 703 consecutive COVID-19 patients hospitalized in the University Clinical Center Kragujevac between September and December 2021. Patients were followed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Laboratory markers associated with increased risk for severe disease include lymphocytopenia, neutrophilia, and elevated serum ALT, AST, LDH, CRP, and ferritin [23,24]. Furthermore, our results agree with the majority of authors [5,7,21,25] in that lymphopenia and elevated values of AST and LDH were statistically significantly more frequent in patients with severe forms of the disease. We can assume that a reduced number of lymphocytes is a consequence of viral attachment, damage to the immune system, or exudation of circulating lymphocytes into the inflammatory lung tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Laboratory markers associated with increased risk for severe disease include lymphocytopenia, neutrophilia, and elevated serum ALT, AST, LDH, CRP, and ferritin [23,24]. Furthermore, our results agree with the majority of authors [5,7,21,25] in that lymphopenia and elevated values of AST and LDH were statistically significantly more frequent in patients with severe forms of the disease. We can assume that a reduced number of lymphocytes is a consequence of viral attachment, damage to the immune system, or exudation of circulating lymphocytes into the inflammatory lung tissue.…”
Section: Discussionsupporting
confidence: 90%
“…When compared to moderate illness, PCT is four times higher in severe patients and eight times higher in critical patients, according to Hu R. et al [ 11 ]. Likewise, several authors found that PCT levels are increased in patients with a fatal outcome of severe COVID-19 both at admission and during the course of hospitalization [ 10 , 12 , 13 ]. In addition, Sayah W. et al assessed that PCT and the neutrophil-to-lymphocyte ratio are not influenced by the administration of CTS.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, other studies reported that patients older than 65 suffering from comorbidities experienced more severe symptoms, MODS and death [ 27 , 58 ]. Hypertension and obesity are the most frequent comorbidities in patients with severe or fatal COVID-19, and the main cause of death after ARDS is a cardiovascular acute event, such as myocardial dysfunction, arrhythmia or shock [ 10 , 12 , 13 , 26 , 59 , 60 ]. Instead, according to other authors, COVID-19-deceased patients presented, at admission, more frequently with chronic kidney disease and neurological diseases [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common laboratory abnormalities seen in hospitalized COVID-19 patients include lymphocytopenia accompanied by an elevated neutrophil count, thrombocytopenia, anemia, raised LDH levels, D-dimer, CRP, liver enzymes, and decreased albumin levels [ 67–69 ]. Specific markers, such as lymphocytopenia, neutropenia, elevated serum liver enzymes, LDH, CRP, and ferritin, have been associated with an elevated risk of severe disease [ 66 , 70 , 71 ]. Elevated levels of CRP and reduced albumin levels are crucial indicators of severe disease progression [ 72 , 73 ], indicating the development of cytokine storm in COVID-19 patients.…”
Section: Laboratory Findings Of Covid-19 Patientsmentioning
confidence: 99%